Analisis Fasilitas Pariwisata Menggunakan Prosedur Pengambilan Keputusan N-Soft Set - Fatia Fatimah; Andriyansah (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Conflict resolution plays an important role in organizations such as in business, government, politics, etc. Some management systems make a conflict as an effort to explore the ability of their employees in rational thinking. Unfortunately, conflict situations tend to be uncertain. It is very difficult to make decisions in rational manner. In this paper, we used -soft sets approach to handle such conflict problems. The proposed algorithm was applied to the real tourism data. The -soft sets algorithm for conflict analysis is effective for decision making problems. The results showed that public transportations and place of worships are very good in Gili Trawangan, Senggigi, Sembalun, and Pantai Kuta, West Nusa Tenggara.